1-second-resolved strain mapping in Ti-6Al-4V alloys during dwell fatigue in SEM by video sampling moiré. (June 2019) - Wang, Qinghua; Ri, Shien; Maenosono, Akira; Tanaka, Yoshihisa; Koyama, Motomichi
Highlights: 1 second-resolved strain mapping in scanning electron microscope (SEM) is realized. Dynamic microscale strain distribution of Ti-6Al-4V in SEM is first reported. Strain rates of average and maximum strains of Ti-6Al-4V in dwell fatigue are measured. Strain evolution on grains and concentration near crack tip are visually observed. Experimental plastic strain increment is a benchmark to establish simulation models. Abstract: Towards clarifying underlying behavior of dwell fatigue in Ti alloys, we here present the first example of 1 second- and 1 μm-resolved full-field dynamic strain mapping. It has been realized by developing a video sampling moiré method combined with a video acquisition way in a scanning electron microscope (SEM). Monotonic strain increments during displacement holding for 10 min in dwell fatigue are visually characterized in both smooth and cracked Ti-6Al-4V specimens. The strain rates from 10 −6 to 10 −5  s −1 of average and maximum strains, as well as the remaining plastic strain were experimentally measured in both specimens. The strain distributions are coupled with grain boundaries to discuss the strain evolution characteristics. Experimental results indicate that both crack initiation and growth in the Ti-6Al-4V alloy are sensitive to even several tens of second-scale load/displacement holding. Graphical abstract: Image, graphical abstract